eCM 2013
DOI: 10.22203/ecm.v026a07
|View full text |Cite
|
Sign up to set email alerts
|

A new take on an old story: chick limb organ culture for skeletal niche development and regenerative medicine evaluation

Abstract: Scientific research and progress, particularly in the drug discovery and regenerative medicine fields, is typically dependent on suitable animal models to develop new and improved clinical therapies for injuries and diseases. In vivo model systems are frequently utilised, but these models are expensive, highly complex and pose a number of ethical considerations leading to the development and use of a number of alternative ex vivo model systems. The ex vivo embryonic chick long bone and limb bud models have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 95 publications
0
54
0
Order By: Relevance
“…When limb buds are isolated from the embryo and placed as intact explants in organ culture, they remain viable for several days, but grow and develop slowly (Neubert et al, 1974; Smith et al, 2013). We exploited this explant culture system to further interrogate the developmental properties and action of KGN.…”
Section: Resultsmentioning
confidence: 99%
“…When limb buds are isolated from the embryo and placed as intact explants in organ culture, they remain viable for several days, but grow and develop slowly (Neubert et al, 1974; Smith et al, 2013). We exploited this explant culture system to further interrogate the developmental properties and action of KGN.…”
Section: Resultsmentioning
confidence: 99%
“…The avian limb bud model was utilised to examine the effects of local microinjection of staurosporine, zinc chloride and growth factors on extra digit formation via the induction of interdigital tissue chondrogenesis [ 103 ]. Microinjection into the chick femur of chick preosteoclast cell populations, which are normally not present in the immature femur in ovo, results in signifi cant bone resorption and remodelling within the femur, when stimulated with factors such as PTH and PTHrP that are involved in bone resorption and remodelling in vivo [ 84 ]. Endothelial cells labelled with fl uorescent trackers can be microinjected into embryonic chick femur organotypic cultures that are coupled with the CAM model to dissect the mechanisms of blood vessel formation and invasion in a dynamic ex vivo microenvironment [ 84 ].…”
Section: Modulation Of Skeletal Development In Organotypic Cultures Bmentioning
confidence: 99%
“…Historically, bone/limb organ cultures were developed as an alternative ex vivo model to investigate the effects of factors and conditions on the temporal stages of cartilage/bone development, modulation and repair [ 83 ]. This technique has been modifi ed over the years to include the culture, at the air-liquid interface, of limb buds and bones (of both avian and mammalian embryos) on stainless steel meshes or porous fi lter membranes, placed in tissue culture plates supplemented with the appropriate culture medium [ 84 ]. Organ cultures predominantly utilise serum-free medium to accurately defi ne the culture conditions that can be obscured by the use of foetal calf serum [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a growth and developmental difference between avian and mammalian bone which could raise doubts in the interpretation of the experimental results for clinical application. 17 Farquharson and Jefferies, 18 and Nowlan et al, 19 reported that the secondary ossification centre of embryonic avian bone is absent before hatching, but does occur in mammalian fetal bone. The primary cartilage in fetal chick bones lacks vascular supply prior to mineralisation.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of this research utilises pathogen-free chick embryos. 17,22 Ex vivo bone growth models and development studies, other than embryonic avian and rodent models, are summarised in Table I. 12,23-35 …”
Section: Introductionmentioning
confidence: 99%